Coping Strategies of Patients’ Undergoing Hematopoietic Stem Cell Transplantation in Pakistan - Shah, Ayaz Hussain; Raisa Gul; Summaira Nasir; Falak Hamid; Mir, Muhammad Ayaz; Ghulam Ishaq (Medical Journal of South Punjab, 2025)
Aim: To explore the coping strategies used by the patients during HSCT in Pakistan. Study Design: A qualitative exploratory descriptive research design was used in this study. Place and duration: The study was conducted in the BMT unit at Quaternary Care Hospital in Pakistan, from February 2019 to April 2020. Methodology: 11 participants were included in the study via purposive sampling. Daily diary writing by the patients in response to the semi-structured interview guide was the main strategy of data collection followed by individual interviews and observations, as and when required. Data were analyzed for the theme and sub-themes following the Elo and Kygnas process of inductive qualitative content analysis. Results: The data analysis revealed seven categories, including “Spirituality and Faith,” “Familial and Social Support,” “Walking,” “Seeking and Sharing Information,” “Rationalization and Optimism,” “Remarks of Encouragement,” and “Days Count Down,” that describe the specified coping strategies used by the patients during HSCT. Conclusion: The study findings revealed that the patients in Pakistan cope with physical and psychological hardships during HSCT primarily by relying on spiritual and religious practices. Moreover, the remarks of encouragement, familial and social support, walking, rationalization and optimism, and day’s countdown strategy also helped the patients preserve their emotional integrity.